2014
DOI: 10.1002/ijc.28988
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary cancers as a guide to heritability

Abstract: There are approximately 100 genes which when mutated are known to predispose to one or more forms of cancer. Currently, genetic testing is offered for many of these, either as single genes or as multi‐gene panels. Features of hereditary cancer include a positive family history of cancer, early age of onset and the appearance of multiple primary cancers in one individual. In some cases multiple cancers may be of the same site (e.g., bilateral breast cancer) and in other cases they may be at different sites. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 106 publications
(187 reference statements)
1
59
0
Order By: Relevance
“…BAP1 knockdown in MM cell lines has been paradoxically associated to a decreased proliferation, with an accumulation of cells in the S phase of the cell cycle 22 , suggesting that BAP1 loss might promote tumorigenesis inducing a delayed, but more permissive, G1/S checkpoint 22 . Heterozygous germline mutations of other important tumor suppressor genes, such as BRCA1 , CDKN2A , and RB1 , increase risk of cancer specifically to one or very few anatomical sites 39 . One of the few tumor suppressor genes whose germline heterozygosity, similar to BAP1, is associated to increased risk of cancer to several sites is TP53 , which encodes p53 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAP1 knockdown in MM cell lines has been paradoxically associated to a decreased proliferation, with an accumulation of cells in the S phase of the cell cycle 22 , suggesting that BAP1 loss might promote tumorigenesis inducing a delayed, but more permissive, G1/S checkpoint 22 . Heterozygous germline mutations of other important tumor suppressor genes, such as BRCA1 , CDKN2A , and RB1 , increase risk of cancer specifically to one or very few anatomical sites 39 . One of the few tumor suppressor genes whose germline heterozygosity, similar to BAP1, is associated to increased risk of cancer to several sites is TP53 , which encodes p53 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous germline mutations of other important tumor suppressor genes, such as BRCA1 , CDKN2A , and RB1 , increase risk of cancer specifically to one or very few anatomical sites 39 . One of the few tumor suppressor genes whose germline heterozygosity, similar to BAP1, is associated to increased risk of cancer to several sites is TP53 , which encodes p53 39 . Besides its well-known intrinsic functions, recently a novel non-cell-autonomous tumor suppressor effect of p53 has been described, via regulation of macrophage polarization and cytokine release 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary breast ovarian cancer (HBOC) can be defined as a genetic disorder in which breast and ovarian malignant tumors seem to cluster within families . The main factors that suggest a hereditary cancer predisposition syndrome are young age at cancer diagnosis, multiple tumors, bilateral tumors, presence of rare tumors, several cancer‐affected relatives, autosomal dominant inheritance and, in some cases, ethnicity . Families with these characteristics should be referred to specialized hospital/centers that offer cancer risk assessment and genetic counseling…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of multiple primary tumors is relatively rare, especially in young people. Inherited genetic defects are one of the most possible pathogenic factors that predispose young subjects to cancers or multiple primary tumors . Chan et al reported that deleterious germline mutations were identified in one‐third (38/110) of patients with multiple primary tumors, spanning 11 known cancer predisposition genes including BRCA1 , BRCA2 , mismatch repair genes ( MLH1 , MSH2 , MSH6 ), TP53 , APC , ATM , MUTYH , PALB2 , and RAD50 .…”
Section: Introductionmentioning
confidence: 99%